STATE OF PUBLIC BUILDINGS IN GHANA AFTER THE PASSAGE OF THE PERSONS WITH DISABILITY ACT (ACT 715): THE CASE OF TERTIARY INSTITUTIONS - Samuel K. Ansah; Kwaku Owusu (Journal of Construction Project Management and Innovation)
Persons with disability Act (ACT 715) makes it mandatory to put up buildings that are disabled friendly but most designers and contractors in Ghana fail to factor the disabled people in the design and construction of infrastructure. In most cases where attention has been given, the provision of the person with disability has been misconstrued by some building industry players to mean provision of ramps to ground floors. After the passage of the persons with disability Act, in 2006, it has become necessary that all public buildings in Ghana have to be designed and built to incorporate the required features that will aid the disabled to have a comfortable access to all public places. This study is therefore carried out to investigate into the state of public buildings in Ghana after the passage of the persons with disability Act (ACT 715) with particular emphasis on public tertiary educational institution buildings in Ghana. To achieve the study objectives, the paper adopted research survey method which includes the use of questionnaire and interview conducted among Contractors and Clients representatives as well as officials from the Law Enforcing Agency who are directly involved in the construction of public buildings. The study considered four public tertiary institutions and the type of buildings considered under these institutions are lecture halls, students’ hostel, offices and residential flats for staff. The results showed that though the disability law has been passed, out of 31 buildings investigated, 9.68% of the buildings were fully factored with disability facilities, 67.74% partially factored and 22.58% not factored at all. The study concluded that law enforcing agency should ensure that construction professionals fully factor disabled people in their building designs and construction. Massive education should also be given to the general public and clients about the need to make buildings disabled friendly.